IUPHAR ECR review: The cGAS-STING pathway: Novel functions beyond innate immune and emerging therapeutic opportunities - Xu He; Abdalla Wedn; Jian Wang; Yanlun Gu; Hongjin Liu; Juqi Zhang; Zhiqiang Lin; Renpeng Zhou; Xiaocong Pang; Yimin Cui (Elsevier, 2024)
Stimulator of interferon genes (STING) is a crucial innate immune sensor responsible for distinguishing pathogens and cytosolic DNA, mediating innate immune signaling pathways to defend the host. Recent studies have revealed additional regulatory functions of STING beyond its innate immune-related activities, including the regulation of cellular metabolism, DNA repair, cellular senescence, autophagy and various cell deaths. These findings highlight the broader implications of STING in cellular physiology beyond its role in innate immunity. Currently, approximately 10 STING agonists have entered the clinical stage. Unlike inhibitors, which have a maximum inhibition limit, agonists have the potential for infinite amplification. STING signaling is a complex process that requires precise regulation of STING to ensure balanced immune responses and prevent detrimental autoinflammation. Recent research on the structural mechanism of STING autoinhibition and its negative regulation by adaptor protein complex 1 (AP-1) provides valuable insights into its different effects under physiological and pathological conditions, offering a new perspective for developing immune regulatory drugs. Herein, we present a comprehensive overview of the regulatory functions and molecular mechanisms of STING beyond innate immune regulation, along with updated details of its structural mechanisms. We discuss the implications of these complex regulations in various diseases, emphasizing the importance and feasibility of targeting the immunity-dependent or immunity-independent functions of STING. Moreover, we highlight the current trend in drug development and key points for clinical research, basic research, and translational research related to STING.